PHYSICO-MECHANICAL CHARACTERISTIC SOIL ON RESULT OF THE STEADY-STATE FLEXING ON OBJECT REKREATION PURPOSES IN CHERNIGOV - Іванишин, В. А.; Прибитько, І. О.; Корзаченко, М. М.; Шпилька, С. М. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The results of the study physico-mechanical characteristic soil by steady-state flexing on object recreation purposes on peninsula between r. Strizheni and r. Desna in Chernigov are stated. Keywords:flexing, resistance, friction, pile, density.